Cat swarm optimisation-based mobile sinks scheduling in large-scale wireless sensor networks. (9th November 2022) - Boyineni, Srinivasulu; Kavitha, K.; Sreenivasulu, Meruva
In wireless sensor networks (WSNs), the hotspot problem is one of the major challenging issues because it isolates some network parts and interrupts the data routing. The hotspot problem is mitigated through a mobile sink, where it visits a set of nodes in the network called rendezvous points, whereas the remaining nodes traverse their data to it. In large-scale WSNs, the travelling distance of MS is longer, and it increases the delay of reaching an RP. So, the data overflow may occur due to a limited buffer of sensor nodes. This problem is avoided by increasing the number of mobile sinks in the WSNs. In this context, a cat-swarm optimisation algorithm is used to decide the optimal set of mobile sinks and a simple geometric method to determine the optimal visiting order for each mobile sink. The proposed work is compared with start-of-art literature, and the proposed work outperforms them.